2018
DOI: 10.1051/e3sconf/20184005029
|View full text |Cite
|
Sign up to set email alerts
|

Vortex-Resistance Hypothesis: Large Eddy Simulation of Turbulent Flow in Isolated Pool- Riffle Units

Abstract: By numerical simulations of turbulent flow in isolated poolriffle units with various riffle heights, four different types of vortices were found and named as follows: surface rollers (SR), corner rollers (CR), ramp rollers (CR), and axial tails (AT). Surface rollers are shaped on the flow surface due to submerged hydraulic jump or any obstacles in the forced poolriffle units. Corner rollers are shaped close to the corners near the walls at the pool head. Ramp rollers are formed at the bed of the channel on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…This observation is in agreement with previous studies (e.g. Dashtpeyma & Macvicar, 2018; de Almeida & Rodríguez, 2011). Dashtpeyma and Macvicar (2018) reported supercritical flow and strong vortex shedding in numerical simulations of pool‐riffle units with a slope of 0.001 and constant flow.…”
Section: Methodssupporting
confidence: 94%
See 1 more Smart Citation
“…This observation is in agreement with previous studies (e.g. Dashtpeyma & Macvicar, 2018; de Almeida & Rodríguez, 2011). Dashtpeyma and Macvicar (2018) reported supercritical flow and strong vortex shedding in numerical simulations of pool‐riffle units with a slope of 0.001 and constant flow.…”
Section: Methodssupporting
confidence: 94%
“…Dashtpeyma & Macvicar, 2018; de Almeida & Rodríguez, 2011). Dashtpeyma and Macvicar (2018) reported supercritical flow and strong vortex shedding in numerical simulations of pool‐riffle units with a slope of 0.001 and constant flow. Table 1 shows that our feeding methodology resulted on the same value of the relative feeding (feeding weight/hydrograph volume) of 0.04 kg/m 3 for Exps 1, 2 and 4 and a higher value of 0.06 kg/m 3 for Exp 3.…”
Section: Methodsmentioning
confidence: 99%
“…Allen, 2007; Alvarez et al., 2017; Schmidt, 1990), suggesting this is a common occurrence. The velocity dip phenomenon in alluvial riffle‐pool sequences has been ascribed to the presence of large‐scale coherent flow structures that induce convective deceleration of the water surface, impeding downstream flow and pushing the CMV toward the bed (Dashtpeyma & MacVicar, 2018; MacVicar et al., 2013; MacVicar & Rennie, 2012). Our observations suggest that plunging flows may be enhanced or even caused by large‐scale coherent flow structures that decelerate flow, although the backwater‐spilling flow mechanism likely sets up the conditions necessary for plunging flows to occur and to carve deep scour pools in bedrock canyons (cf.…”
Section: Discussionmentioning
confidence: 99%
“…A series of reductionist Froude‐scaled experiments in both smooth and rough channels showed that many key flow features of pool‐riffles could be reproduced in relatively simple pool‐riffle geometries (B. J. MacVicar & Best, 2013; B. J. MacVicar & Obach, 2015; B. J. MacVicar & Rennie, 2012). Preliminary work on similar geometries was completed with large eddy simulation (LES) numerical models (Dashtpeyma & MacVicar, 2018; Stoesser et al., 2010; Tokyay & Sinha, 2020) because this approach is effective for investigating geophysical flows where non‐uniform flow and turbulent mixing occurs such as in shear zones at confluences and meanders (Alvarez & Grams, 2021; Bradbrook et al., 2000; Duguay et al., 2022; Jiang et al., 2022; Kang & Sotiropoulos, 2011; Keylock et al., 2012). In the current study we further develop the LES approach for investigating pool‐riffle hydrodynamics by varying the riffle height in a series of cases designed to approach the threshold for critical flow and induce a possible regime change in the flow.…”
Section: Introductionmentioning
confidence: 99%